The Viability of Lactobacillus plantarum From Intestines of Laying Ducks Encapsulated With Arabic Gum and Skimmed Milk (Faculty of Animal Science Universitas Brawijaya, 2021)
The aim of this study was to evaluate the effect of the types of encapsulation materials, that is skimmed milk and Arabic gum on two probiotics Lactic Acid Bacteria (LAB), including L. plantarum DJ2 and L. plantarum DJ3. The methods of this study were separated into two stages that is probiotic resistance testing during the spray drying process and the viability of LAB after spray drying during storage of probiotic powder for one month at 4oC. Changes in the viability of LAB probiotics before and after the drying process using spray drying were determined by the total plate count. The viability of lactic acid bacteria (LAB) was observed every week for one month of storage at 4oC. The results showed that different encapsulation materials had significant different (P â‰¤ 0.05) on changes in resistance of probiotics powder during spray drying process. The use of Arabic gum could increase the resistance of probiotics during the spray drying process, meanwhile, the use of skimmed milk was better to be able to maintain the viability of dry probiotic powder both on L.plantarum DJ2 and L.plantarum DJ3 during storage. After four weeks of storage, there was mold and yeast in the skimmed milk and Arabic gum materials. In conclusion, both Arabic gum and skim milk could be used for encapsulation where storage of dry probiotic products is recommended during one month at 4 oC.